2002
DOI: 10.1016/s0014-3057(02)00125-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion coefficients of sodium dodecyl sulfate in water swollen cross-linked polyacrylamide membranes

Abstract: Diffusion of aqueous sodium dodecyl sulfate (SDS) across cross-linked polyacrylamide hydrogel membranes has been studied by electrical conductivity measurements. Initial rapid sorption of SDS (as unimer) into the membranes is observed. The effect of SDS concentration, and of cross-linker fraction on the degree of swelling of the gels is studied and associated with binding of the surfactant to the polymer, with surface bound water suggested to be involved in these interactions. Below the surfactant critical mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…This method is applied to the study of diffusion of electrolytes in polymer membranes [13,14]. We are particularly interested in the behaviour of ionic surfactants, and we have previously studied the diffusion of the important anionic detergent sodium dodecyl sulfate (SDS) in poly(acrylamide) gels [15] and in cellulose ester membranes of differing degrees of hydrophobicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…This method is applied to the study of diffusion of electrolytes in polymer membranes [13,14]. We are particularly interested in the behaviour of ionic surfactants, and we have previously studied the diffusion of the important anionic detergent sodium dodecyl sulfate (SDS) in poly(acrylamide) gels [15] and in cellulose ester membranes of differing degrees of hydrophobicity [11].…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion coefficients of acetylsalicylic acid are 1.2 × 10 −7 and 8.5 × 10 −8 cm 2 /s for the cross-linking ratios (mol MBA /mol AAM ) of 0.0115 and 0.02305, respectively (Ferreira et al, 2001). Valento et al (2000) reported a similar effect of cross-linking ratio on the diffusion coefficients of sodium dodecyl sulfate, SDS (drug size ~ 20 Å) in waterswollen cross-linked polyacrylamide membranes in the absence of an electric field. The diffusion of SDS through polyacrylamide hydrogel was measured by using the cell that consists of two components filled with SDS solution and water, respectively.…”
Section: Effect Of Cross-linking Ratiomentioning
confidence: 76%
“…The diffusion coefficient apparently decreases with increasing cross-link ratio due to a decreasing matrix pore size. The diffusion coefficients of sodium dodecyl sulfate are 0.5 × 10 −6 , 1.2 × 10 −6 , and 2.5 × 10 −6 cm 2 /s for cross-linking ratios (mol MBA /mol AAM ) of 0.032, 0.0032, and 0.0014, respectively (Valento et al, 2000).…”
Section: Effect Of Cross-linking Ratiomentioning
confidence: 96%
See 1 more Smart Citation
“…For surfactant solution @r=@T was taken from experimental r(C) measurements, Table 1, D is about 10 À10 m 2 /s, Valente et al [24].…”
Section: Flow Visualizationmentioning
confidence: 99%